Vascular anomalies. Issue 5 (May 2021) - Gokani, Vimal J.; Sivakumar, Branavan; Kangesu, Loshan
Abstract: Vascular anomalies are vascular lesions that are present from childhood. They are classified into tumours or malformations based on clinical and histological features. Benign infantile haemangiomas are the most common vascular tumour and have a predictable self-limiting course. Rarer vascular tumours exist, and some may cause platelet consumption. Management is usually conservative, with active treatment reserved for functional or cosmetic complications (ulceration, or obstruction and distortion of vital structures). Oral propranolol is useful for troublesome lesions. Vascular malformations are structural anomalies of vascular morphogenesis present at birth without cellular proliferation that, in general, grow with the patient. They are sub-classified by vessel type as 'low flow' (capillary, lymphatic and venous) and 'high flow' (arteriovenous) or lesions with a combination of vessel type. They become problematic under certain circumstances, usually puberty and also pregnancy. The most troublesome are extensive lesions, especially venous and arteriovenous. Their effects may be cosmetic, those of a space-occupying lesion, infection, bleeding, pain or coagulopathy. Venous lesions cause consumptive coagulopathy, sometimes with life-threatening risks. Treatment options include medication and symptom control with antibiotics, analgesia, control of menses, compression garments and intervention with laser (capillary type), sclerotherapy, embolization and/or surgical excision. Patients with complex lesions, are best managed by a multidisciplinary team and all surgical sub-specialties may be involved.